Leśmian Internationally: Contextual Relations A Comparative Study - Nalewajk-Turecka, Żaneta (Polish Studies - Transdisciplinary Perspectives, 2020)
This book shows the literary legacy of Bolesław Leśmian, the great Polish writer, as engaged in a dialogue with the tradition, and forged on the crossroads of literatures, and epochs. Exploring American, French and Russian contexts (Poe's writing, Baudelaire's oeuvre, Balmont's texts, the symbolist style, the bylinna tradition), highlighting the correspondences between Leśmian and the romantics (Pushkin, Gogol) as well as the modernists (Jesienin, Gorodetsky) and connecting his work to Ukrainian culture through the evocation of old Slavic folklore, the book showcases Leśmian's work as an example of interliterary and inter-cultural transfer of aesthetics, styles, genres and motifs. A crucial outcome of this research is the codifying of a contextual analysis as a method of comparative studies.